Does the African charter on the rights and welfare of the child (ACRWC) only underlines and repeats the convention on the rights of the child (CRC)’s provisions?: examining the similarities and the differences between the ACRWC and the CRC (2015)
The Convention on the Rights of the Child (CRC) is the first legally binding international instrument to address specifically children’s rights comprehensively. It is the most widely ratified human rights treaty in the world. The African Charter on the Rights and Welfare of the Child (ACRWC) was adopted in 1990. It is designed to retain the spirit as well as substance of the letter of the CRC while at the same time having special provisions guided by the situations in Africa. There are several similarities in the provisions of the two child's rights instruments. The paper examines the question whether there is need for a regional treaty on the rights of the child apart from the CRC which is global. The objective of the paper is to show whether both treaties have complemented and reinforced each other